2000
DOI: 10.1038/sj.bmt.1702521
|View full text |Cite
|
Sign up to set email alerts
|

High-dose melphalan and allogeneic peripheral blood stem cell transplantation for treatment of early relapse after allogeneic transplant

Abstract: Summary:Patients with acute leukemias relapsing within 1 year of an allogeneic BMT have a poor prognosis. We studied the use of melphalan 180 mg/m 2 followed by allogeneic peripheral blood stem cells (PBSC) as salvage treatment for patients relapsing after related (n = 7) or matched unrelated transplants (n = 3). Diagnoses were AML (n = 4), ALL (n = 3), biphenotypic acute leukemia (n = 2) and CML in blast crisis (n = 1). Eight patients were beyond first relapse and none were in remission. The median time from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This is likely related to the refractory nature of disease in most of our patients, given the early time to relapse following the first transplant procedure. [6][7][8]31 This low intensity conditioning regimen by itself, while having some antileukemic activity, is unlikely to sustain a remission in patients with advanced AML, as has been suggested previously by de Lima et al 31 Others have also suggested that employing a less intensive pretransplant conditioning may increase the risk of relapse in patients with AML. 32 Four of the five patients who suffered relapse never developed acute or chronic GVHD prior to the onset of relapse.…”
Section: Discussionmentioning
confidence: 84%
“…This is likely related to the refractory nature of disease in most of our patients, given the early time to relapse following the first transplant procedure. [6][7][8]31 This low intensity conditioning regimen by itself, while having some antileukemic activity, is unlikely to sustain a remission in patients with advanced AML, as has been suggested previously by de Lima et al 31 Others have also suggested that employing a less intensive pretransplant conditioning may increase the risk of relapse in patients with AML. 32 Four of the five patients who suffered relapse never developed acute or chronic GVHD prior to the onset of relapse.…”
Section: Discussionmentioning
confidence: 84%
“…All other regimens were categorized as reduced-intensity regimens. 10 Myeloablative preparative regimens included cyclophosphamide in combination with intravenous busulfan (seven patients) or total body radiation7thiotepa (five patients); 11,12 decitabine (eight patients); 13 single agent melphalan (13 patients); 14 intravenous busulfan in combination with fludarabine (two patients), or cyclophosphamide and thiotepa (three patients). 15,16 Reduced-intensity regimens included fludarabine, cytarabine, and idarubicin or cisplatin (two patients), fludarabine and melphalan with/without antithymocyte globulin (19 patients); [17][18][19] fludarabine plus antithymocyte globulin (six patients); fludarabine plus intravenous busulfan (one patient); gemtuzumab ozogamicin, fludarabine, and cytarabine (four patients) or melphalan (one patient).…”
Section: Conditioning Regimens For Second Transplant Proceduresmentioning
confidence: 99%
“…5 Melphalan (MEL) is an alkylating agent with demonstrated activity in acute leukemia. 6 A reduced-intensity preparative regimen of FLU and MEL leads to durable engraftment in sibling and unrelated HSCT in adult patients. [7][8][9] However, this approach has not been evaluated in childhood leukemia.…”
Section: Introductionmentioning
confidence: 99%